DAMPAK KEBIJAKAN TARIF IMPOR GULA TERHADAP KESEJAHTERAAN PRODUSEN DAN KONSUMEN - Anna Fariyanti (Jurnal Agribisnis dan Ekonomi Pertanian, 2007)
The Government has used a sugar import tariff policy to protect the domestic sugar producers from sugar import competition. The objective of this paper is to analyze the effects of sugar import tariff policy on producers’, consumers’, government and economic welfare. The policy of increasing sugar import tariff will lead to decreasing consumers’ welfare; on the contrary, producers’ welfare and government revenue will increase. Meanwhile, this policy will reduce economic welfare.